SCREENING OF INDIGENUS BACTERIA’S DEGRADING OF HYDROCARBON PETROLEUM FROM POLLUTED SEA AT BANDAR LAMPUNG’S DOCK - Yuni Lisafitri; Tastaptyani Kurnia Nufutomo; Fitralia Elyza (Journal of Environmental Engineering and Sustainable Technology, 2019)
Indonesia is committed to achieving the SDGs in 2030. One of SDGs is protect the marine ecosystem. Bandar Lampung which has a coastal area in a form of a dock for sea transportation and the anchoring of fishing boats. These area are starting to be polluted due to waste, one of which is the fuel waste of ships or fishing boats that are in the area. When the quality of sea water decreases due to pollution it will have an impact on population and diversity of marine life. If this happens the sea will be damaged and the income of fishermen will decrease. Various studies have been conducted to overcome problems caused by oil (petroleum hydrocarbons), especially research on the use of microbiology in remediating polluted environments. Therefore, this study was conducted to test P1 isolates isolated from sea water in docks around Bandar Lampung. The Measurement was carried out at The Integrated Laboratory of ITERA by observing the growth of the bacteria (population of bacteria) on selective media that had been added with diesel oil as much as 2% (v/v). This measurement was carried out on day 1, day 4 and day 7 after incunbation for population and for % TPH was measurement in the first day and the last day of incubation. The results obtained that the GT1 isolate have a good result in population and decreasing of TPH than the other isolate.